Development of a Model of Holistic Reflection to facilitate transformative learning in student midwives. Issue 3 (June 2017) - Bass, Janice; Fenwick, Jennifer; Sidebotham, Mary
Abstract: Background: Reflective practice is considered an essential aspect of personal and professional development, and critical reflection is considered the cornerstone of being an accountable and autonomous practitioner. Tertiary education should lay the foundations of lifelong learning by ensuring students develop into critically reflective and reflexive practitioners, who demonstrate self-awareness and an ability to reflect on personal values and beliefs and their impact on the wider healthcare system. This level of reflective practice is essential to effect change at both an individual and societal level. Reflection should therefore be embedded into education programs as a learning, teaching and assessment strategy. Aim: The aim of this paper is to describe a structured Model of Holistic Reflection embedded within an Australian Bachelor of Midwifery Program. The paper firstly outlines the theoretical and conceptual underpinnings of the newly developed model. Secondly describes the six integrated and inter-dependant phases of the model. Discussion and conclusion: The aim of developing the Holistic Reflective Model was to produce a sound educational tool to assist midwifery students to progressively build reflexivity and reflective practice. Furthermore, provide midwifery academics with an educational resource to facilitate development of reflective and critical thinking skills in students. The specific intention was to promote deep personal and transformative learning across an entry to practice program. This paper highlights a number of ways the model can be embedded within the curriculum to support the scaffolded development of critical reflection and reflexivity required to facilitate transformative learning. While evaluation is required the model may have transferability to other disciplines.